(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The hand held vegetable transplanted consists of different component like handle, lever, hollow pipe, jaw and jaw operating wire. The implement penetrates into soil by its self weight hold with handle, seedling is dropped into hollow pipe then the jaw opened with lever. This work is focused on design, development and testing of hand held vegetable transplanted capable to transplant seedling precisely in a straight line with uniform depth in mulch bed. The work demonstrates the application of engineering techniques to reduce the labour efforts and time required for transplanting. The result obtained from the trial tests concluded that transplanter functioned properly as there is no miss planting compared with automatic vegetable trans-planter, also the rate of tilted planting is negligible. The cost of operation is comparatively less than traditional method of transplanting. From visual observation we have seen that there is no damage to the seedling during operation. The transplanting capacity observed from trail is 0.02 ha/hr, theoretical field capacity is 0.0243 ha/hr, field efficiency is 82.30%.